PEMILIHAN UMUM, KAMPANYE POLITIK DANPOLITIK UANG MENURUT AL-QUR’AN: Kajian Tafsir Tematik - Muhammad Makmun (STAI AL-ANWAR SARANG, 2025)
General elections, political campaigns, and money politics are central issues incontemporary politics, as they significantly affect regime legitimacy, politicalparticipation, and governance integrity. This study examines the Qur’anicperspective on these three concepts and analyzes their relevance to contemporarypolitical practices. Using a thematic quranic interpretation approach, the researchsystematically analyzes relevant Qur’anic verses to construct a normative ethicalframework. The findings reveal that the Qur’an conceptualizes elections as anideal mechanism for leadership selection, emphasizing sincerity, merit, and theprevention of corruption. Political campaigns are considered permissible insofaras they remain consistent with Islamic moral values, as illustrated by the narrativeof Prophet Joseph (peace be upon him), who assumed public office based oncompetence, and the account of Prophet Shuʿayb’s daughter recommendingMoses, reflecting ethical advocacy. In contrast, political money is identified as aserious ethical violation that undermines public morality, justice, and social trust.This study contributes to strengthening the literature on Islamic political ethicsby presenting an integrated Qur’anic vision. This perspective offers a normativeframework for addressing contemporary political challenges—particularly theinfluence of money politics and unregulated campaign financing—through thereinforcement of transparency, justice, and equal opportunities amongcandidates.